Characteristic measurements of silicon dioxide aerogel plasmas generated in a Planckian radiation environment - Dong, Quan-Li, author; Wang, Shou-Jun, author; Li, Yu-Tong, author; Zhang, Yi, author; Zhao, Jing, author; Wei, Hui-Gang, author; Shi, Jian-Rong, author; Zhao, Gang, author; Zhang, Ji-Yan, author; Gu, Yu-Qiu, author; Ding, Yong-Kun, author; Wen, Tian-Shu, author; et al. (Colorado State University. Libraries, 2010)
The temporally and spatially resolved characteristics of silicon dioxide aerogel plasmas were studied using x-ray spectroscopy. The plasma was generated in the near-Planckian radiation environment within gold hohlraum targets irradiated by laser pulses with a total energy of 2.4 kJ in 1 ns. The contributions of silicon ions at different charge states to the specific components of the measured absorption spectra were also investigated. It was found that each main feature in the absorption spectra of the measured silicon dioxide aerogel plasmas was contributed by two neighboring silicon ionic species.
Keywords: leptons; plasma confinement; x-ray spectroscopy; chemical elements; electron density; absorption spectroscopy; transition metals; electronic configuration; aerogel; silicates